Gaming the Data. How the Finnish School Audit Saved the Profession from New Public Management - Turunen Jaakko (Journal of Organizational Sociology)
Dynamics connected to professionalization are often analysed from an individual perspective highlighting individual professionals’ struggle for recognition as a professional. This paper looks at the organizational context and its effects on teachers’ professional status in the wake of NPM inspired reforms in Finland. Despite the quantitative nature of the Finnish school audit, the design of the evaluation presents a critical translation of the knowledge claims often made in New Public Management audits. By looking at the original research reports and discussions on the audit system, this paper shows how the Finnish school audit conceptualised education as a societal subsystem and school audit as a tool for linking education with other subsystems. The Finnish school audit produces data for educational policy development and the teachers’ own use. The article suggests that maintaining occupational professionalism requires both the presence of knowledge for professional application and the absence of knowledge yielding to market or managerial interference.